Glucose variability in maintenance hemodialysis patients with type 2 diabetes: Comparison of dialysis and nondialysis days. Issue 2 (9th February 2023) - Bomholt, Tobias; Rix, Marianne; Almdal, Thomas; Knop, Filip K.; Rosthøj, Susanne; Jørgensen, Morten B.; Feldt‐Rasmussen, Bo; Hornum, Mads
Abstract: Introduction: Hemodialysis (HD) induces several physiological changes that can affect plasma glucose levels in patients with diabetes and in turn their glycemic control. Studies using continuous glucose monitoring (CGM) to assess glucose variations on dialysis days compared with nondialysis days report conflicting results. Here, we used CGM to examine glucose variations induced by HD in patients with type 2 diabetes. Methods: Patients with type 2 diabetes undergoing maintenance HD were included. CGM (Ipro2®, Medtronic) was performed at baseline and Week 4, 8, 12, and 16 for up to 7 days at each visit. CGM profiles on days where participants received HD were compared with days without HD using a linear mixed model. Findings: Twenty‐seven patients were included. The median number of CGM days performed was 8 (interquartile range [IQR] 6–10) for dialysis days and 16 (IQR 12–17) for nondialysis days. The median sensor glucose was 9.4 (95% confidence interval [CI] 8.8–10.2) mmol/L on dialysis days compared with 9.5 (95% CI 8.9–10.2) mmol/L on nondialysis days ( p  = 0.58). Nocturnal mean sensor glucose was higher on dialysis days compared with nondialysis days: 8.8 (95% CI 8.0–9.6) mmol/L versus 8.4 (95% CI 7.7–9.2) mmol/L ( p  = 0.029). Discussion: Similar median sensor glucose values were found for days on and off HD. Nocturnal glucose levels were modestly increased on dialysis days. Our findings indicate that antidiabetic treatment does not need to be differentiated on dialysis versus nondialysis days in patients with type 2 diabetes undergoing maintenance HD.